PERANCANGAN SISTEM INFORMASI CUSTOMER RELATIONSHIP MANAGEMENT (CRM) (Studi Kasus : CV. Berkah Utama) - Rico (JOURNAL VISION TECHNOLOGY (V-TECH) ISSN : 2622-9315 (Online - Elektronik), 2020)
CV. Berkah Utama was founded in 2000 in Jambi. The company is engaged in travel services such as airplane tickets, sailboats and hotel vouchers. The services available at the company today are less personalized to focus on customers. This resulted in the company not getting a more optimal value and not on target. Therefore we need a business strategy to optimize marketing, sales and service. The research objective is to design a Customer Relationship Management (CRM) system on the CV. Main Blessings that can be used to maintain company relationships with Web-based customers. The model for system development is the Rapid Application System (RAD). the system design is done by using Unified Model Language (UML) tools.